2019
DOI: 10.1063/1.5124674
|View full text |Cite
|
Sign up to set email alerts
|

Strain in InP/ZnSe, S core/shell quantum dots from lattice mismatch and shell thickness—Material stiffness influence

Abstract: We investigate the buildup of strain in InP quantum dots with the addition of shells of the lower-lattice constant materials ZnSe and ZnS by Raman spectroscopy. Both materials induce compressive strain in the core, which increases with increasing shell volume. We observe a difference in the shell behavior between the two materials: the thickness-dependence points toward an influence of the material stiffness. ZnS has a larger Young’s modulus and requires less material to develop stress on the InP lattice at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…Although shell growth has been shown to induce lattice constrain and increase hole trapping time, the thickness of shells are relatively small in our sample ($0.2 nm in InP@ZnS 30 min ) and is unlikely to cause the observed PL changes. 48,49 Recent studies suggested that the growth of the ZnS shell around InP QDs can introduce interior/surface lattice disorder due to the incorporation of Zn 2+ into the InP lattice, 44,50 which introduces new trap states with broad PL emission. 44 We therefore tentatively attribute the observed faster hole trapping rate at long shell growth time to the incorporation of Zn 2+ into the InP lattice.…”
Section: MLmentioning
confidence: 99%
“…Although shell growth has been shown to induce lattice constrain and increase hole trapping time, the thickness of shells are relatively small in our sample ($0.2 nm in InP@ZnS 30 min ) and is unlikely to cause the observed PL changes. 48,49 Recent studies suggested that the growth of the ZnS shell around InP QDs can introduce interior/surface lattice disorder due to the incorporation of Zn 2+ into the InP lattice, 44,50 which introduces new trap states with broad PL emission. 44 We therefore tentatively attribute the observed faster hole trapping rate at long shell growth time to the incorporation of Zn 2+ into the InP lattice.…”
Section: MLmentioning
confidence: 99%
“…Resonance Raman spectra of InP nanocrystals of widely varying sizes and qualities show peaks fairly close to these bulk frequencies plus overtones of these modes. The Raman spectra of bulk ZnSe show mainly the LO phonon at 253 cm –1 , with a much weaker TO phonon at 207 cm –1 . The resonance Raman spectra of pure ZnSe QDs show almost exclusively the LO phonon, shifted to slightly lower frequencies in smaller QDs, and its overtones. , InP/ZnSe core/shell QDs have also been examined by several groups. , The resonance Raman spectra of these materials exhibit phonons similar to those of pure InP and pure ZnSe QDs, but the ZnSe LO phonon, in particular, tends to be shifted to lower frequencies and to have a shoulder between the bulk TO and LO frequencies whose shape and intensity vary greatly. These features, and their interpretation, are further discussed below.…”
Section: Introductionmentioning
confidence: 99%
“…[ 30 ] LO frequencies of InP ESC and InP ESC @ZnS QDs are located at higher frequencies than the LO of InP core‐only QDs because of the compressive force on the InP core lattice with the increase of ZnS shell thickness. [ 31 ] The Raman intensity at 259 cm −1 for ZnS [ 32 ] was gradually enhanced due to the increased ZnS shell thickness.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the InP core is subjected to a compressive force with shell coating due to the smaller lattice constant of ZnS (or ZnSe) compared to that of InP. [ 31 ] The magnitude of the compressive force becomes stronger as the shell thickness increases, and more significant compression is being developed with ZnS shell than ZnSe shell because of relatively larger lattice mismatch of ZnS (7.7%) compared to that of ZnSe (3.5%). The amount of compressive force was relatively larger near the core@shell interfaces than at the core center (Figure 3F,G).…”
Section: Resultsmentioning
confidence: 99%